2020
DOI: 10.1080/09603123.2020.1802409
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the mental health of the adult population in Bangladesh: a nationwide cross-sectional study

Abstract: The recent COVID-19 pandemic has imposed threats on both physical and mental health since its outbreak. This study aimed to explore the impact of the COVID-19 pandemic on mental health among a representative sample of home-quarantined Bangladeshi adults. A cross-sectional design was used with an online survey completed by a convenience sample recruited via social media. A total of 1,427 respondents were recruited, and their mental health was assessed by the DASS-21 measure. The prevalence of anxiety symptoms a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
187
7
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(225 citation statements)
references
References 29 publications
14
187
7
7
Order By: Relevance
“…The current COVID-19 pandemic has exerted psychological and financial impacts on many people (Banna et al, 2020;Bodrud-Doza et al, 2020;Islam et al, 2020c;Zubayer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The current COVID-19 pandemic has exerted psychological and financial impacts on many people (Banna et al, 2020;Bodrud-Doza et al, 2020;Islam et al, 2020c;Zubayer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Public places and schools were briefly re-opened in late May, only to be shut down a few weeks later when the third wave of virus outbreak hit the city (surging new cases had been documented since June 22nd). Such prolonged isolation and changes of daily routine are likely to cause psychological and emotional distress among the public and students [4][5][6][7]. One possible reason is that disease control measures such as social isolation make it more difficult for people to satisfy one of their fundamental psychological needs, that of belongingness [14].…”
Section: Depressive Symptoms and Peer Relationships In The Time Of Pamentioning
confidence: 99%
“…To recap, under the impact of COVID-19, individuals around the globe have been experiencing psychological problems such as elevated depressive symptoms [4][5][6][7]. Some public health measures such as school closures and social distancing helped contain the spread of virus, but also prevented people, especially students, from satisfying their need to connect to others.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Hossain et al (2020) reported that the spread of misinformation from social and electronic media can put extra pressure on mental health stress during the COVID-19 outbreak. A recent study by Banna et al (2020) stated that the COVID-19 among adult populations in Bangladesh interrupted the lifestyle behavior affecting job sectors, mental health stress, the economy, and education systems. Nevertheless, there is a lack of evidence of the mass media in uence on lifestyle behavior changes of community people, especially from Bangladesh during the COVD-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%